Efek Iklim Komunikasi Pada Peningkatan Critical Thinking Skills Peserta Didik - Anita Trisiah (Wardah, 2018)
Abstract This study entitled "The Effects of Communication Climate on Increasing Student Critical Thinking Skills". It is a research that focuses on the state of communication in an organization, in this case, education. Communication climate is a variable which is often researched, yet in educational organizations is still very rare. With the aim to find out how the communication climate effects on increasing critical thinking skills of students, this research will be carried out using qualitative descriptive methods. The data collection techniques used in this study are interviews, observation and documentation. While the main informants were teachers at Sekolah Alam Palembang and supporting informants were students at the SM level. After analyzing the data collected, it was found that a conducive communication climate at Sekolah Alam Palembang (SAPA) was reflected through the dimensions of trust, honesty, joint decision makers, openness in communication downwards, listening to communication upwards, and attention to high performance goals have an impact on increasing critical thinking skills of students which can be seen in the ability to explore information, process information and solve problems creatively based on the information that has been obtained. The communication climate at Sekolah Alam Palembang (SAPA) was also supported by the environment and facilities that support the formation of the creative mindset of teachers to continue to provide stimulants to students become even more critical. Keywords: communication climate, critical thinking skills, students